Reply to Comments on "Synthesis, Characterization, and Structures of Persistent Aniline Radical Cation"1. Issue 4 (18th December 2013) - Chen, Xiaoyu; Wang, Xingyong; Sui, Yunxia; Li, Yizhi; Ma, Jing; Zuo, Jinglin; Wang, Xinping
<x xml:space="preserve">Abstract</x> The identification of the aniline radical cation TBA.+ (TBA=2, 4, 6‐tBu3C6H2NH2) reported in 2012 was questioned in the preceeding Correspondence articles. The original authors have reexamined their UV/Vis absorption and EPR data and insist that TBA.+ radical cation is indeed persistent and stable. The possible cocrystallization of TBA.+ with TBAH+ makes crystal structures more complicated.